ANALISIS LAJU PERTUMBUHAN KONTRIBUSI PAJAK HOTEL, PAJAK RESTORAN, PAJAK HIBURAN, DAN RETRIBUSI PARKIR PADA PENDAPATAN ASLI DAERAH KOTA KEDIRI TAHUN 2020-2025 - Orlen Raffa Dzaky Putra Sukmono; Badrus Zaman; Andy Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the growth rate and contribution of Hotel Tax, Restaurant Tax, Enter-tainment Tax, and Parking Retribution to the Locally-Generated Revenue (Pendapatan Asli Daerah/PAD) of Kediri City during the 2020-2025 period. The research was motivated by fluctuating realization of these four regional revenue components as parts of PAD. A quanti-tative approach with a descriptive method was used. Data were collected through documen-tation of PAD realization reports obtained from the Regional Finance and Asset Manage-ment Agency (BPKAD) of Kediri City. The population comprised all PAD realization data of Kediri City, while the sample consisted of realization data of Hotel Tax, Restaurant Tax,Entertainment Tax, Parking Retribution, and total PAD of Kediri City for the 2020-2025 period. The results show that the growth rates of the four revenue sources tended to fluctuate. Restaurant Tax provided the largest contribution to PAD, while Hotel Tax, Entertainment Tax, and Parking Retribution still had relatively low contributions. Therefore, optimization of the management and collection of regional taxes and retributions needs to be continuously improved to sup-port the increase of Kediri City's PAD.